Turnover and function of noncoding RNA polymerase II transcripts. - Dye, M; Gromak, N; Haussecker, D; West, S; Proudfoot, N (2006)
In the past few years, especially since the discovery of RNA interference (RNAi), our understanding of the role of RNA in gene expression has undergone a significant transformation. This change has been brought about by growing evidence that RNA is more complex and transcription more promiscuous than has previously been thought. Many of the new transcripts are of so-called noncoding RNA (ncRNA); i.e., RNA that does not code for proteins such as mRNA, or intrinsic parts of the cellular machinery such as the highly structured RNA components of ribosomes (rRNA) and the small nuclear RNA (snRNA) components of the splicing machinery. It is becoming increasingly apparent that ncRNAs have very important roles in gene expression. This paper focuses on work from our laboratory in which we have investigated the roles and turnover of ncRNA located within the gene pre-mRNA, which we refer to as intragenic ncRNA. Also discussed are some investigations of intergenic ncRNA transcription and how these two classes of ncRNA may interrelate.